Composition of growth factors and cytokines in lysates obtained from fresh versus stored pathogen-inactivated platelet units. Issue 3 (December 2016) - Sellberg, Felix; Berglund, Erik; Ronaghi, Martin; Strandberg, Gabriel; Löf, Helena; Sommar, Pehr; Lubenow, Norbert; Knutson, Folke; Berglund, David
Abstract: Background: Platelet lysate is a readily available source of growth factors, and other mediators, which has been used in a variety of clinical applications. However, the product remains poorly standardized and the present investigation evaluates the composition of platelet lysate obtained from either fresh or stored pathogen-inactivated platelet units. Materials and Methods: Platelet pooled units (n = 10) were obtained from healthy blood donors and tested according to standard procedures. All units were pathogen inactivated using amotosalen hydrochloride and UVA exposure. Platelet lysate was subsequently produced at two separate time-points, either from fresh platelet units or after 5 days of storage, by repeated freeze-thaw cycles. The following mediators were determined at each time-point: EGF, FGF-2, VEGF, IGF-1, PDGF-AB/BB, BMP-2, PF4, TGF-β isoform 1, IL-1β, IL-2, IL-6, IL-10, IL-12p70, 1L-17A, TNF-α, and IFN-γ. Results: The concentration of growth factors and cytokines was affected by time in storage. Notably, TGF-β, PDGF-AB/BB, and PF4 showed an increase of 27.2% (p < 0.0001), 29.5% (p = 0.04) and 8.2% (p = 0.0004), respectively. A decrease was seen in the levels of IGF-1 and FGF-2 with 22% (p = 0.041) and 11% (p = 0.01), respectively. Cytokines were present only in very low concentrations and all other growth factors remained stable with time in storage. Conclusion: The composition of mediators in platelet lysate obtained from pathogen-inactivated platelet units differs when produced from fresh and stored platelet units, respectively. This underscores the need for further standardization and optimization of this important product, which potentially may influence the clinical effects.